176 Evaluating Dual-purpose Wheat Varieties in the Southeastern U.S. (8th October 2021) - West, Micayla H; Carrell, Russell C; Dillard, Sandra L
Abstract: Dual-purpose wheat (Triticum aestivum L.) systems increase farm sustainability by diversifying on-farm income. While these systems are common in the Southern Great Plains of the United States, they are not often utilized in the Southeast. This study aimed to evaluate pre- and post-grazing herbage mass (HM) of four winter wheat varieties managed under a dual-purpose grazing and grain production system. The winter wheat varieties evaluated were generic feed-type wheat (mixed variety, Feed), seed-type wheat ('GA Gore') and two forage-type varieties, 'AGS 2024' (AGS) and 'Pioneer 26R41' (Pioneer). The experiment was a completely randomized block design with n = 4. Each plot was randomly assigned either as no-grazing (CON) or grazing (GF2). Plots were grazed with cow-calf pairs that were fasted 24 h before each grazing event. Grazing was considered complete when the average stubble height was 10 cm. Herbage mass was determined using three 0.1m 2 -quadrats per plot and clipping to a 10 cm stubble height before (PreG) and after (PostG) each grazing event. Forage samples were then dried at 45°C for 72 h. Data were analyzed using PROC GLIMMIX of SAS (SAS Inst., Cary, NC). Differences were declared at P < 0.05. Initial HM was greater for PreG than PostG (883 and 615 kg/ha, respectively; P < 0.01). Prior to grazing, AGS (1204 kg/ha) was greater (P < 0.02) than all other varieties. Pre-grazing, there were no differences among the other varieties (776 kg/ha; P > 0.14). Post-grazing, AGS had a greater HM than Seed (788 and 391 ka/ha, respectively; P = 0.04), while all other varieties were intermediate (642 kg/ha). Herbage mass was affected by grazing frequency with CON being greater (P < 0.01) than GF2 (993 and 691 kg/ha, respectively). These results indicate that both wheat variety and grazing treatment had an effect on dual-purpose wheat herbage mass.